Increase in veterinary prescriptions of azithromycin during the COVID-19 pandemic in Brazil - Fernando de Sá Del Fiol; Cristiane de Cassia Bergamaschi; Isaltino Pereira de Andrade; Marcus Tolentino da Silva; Silvio Barberato-Filho; Bianca Gianola Bellini Silva; Andrea Cristina Higa Nakaghi; Luciane Cruz Lopes (Journal of Infection in Developing Countries)
Introduction: With the advent of the pandemic in 2020 and the lack of perspectives on the treatment of COVID-19, numerous therapeutic proposals have emerged, including hydroxychloroquine and azithromycin. Therefore, some studies have shown that in many countries, the demand for azithromycin has increased during the pandemic. In Brazil, antibiotics can only be purchased with a medical, dental, or veterinary prescription. This study aimed to determine whether the number of prescriptions made by veterinarians (which could be used by humans) has increased during the pandemic.